2002
DOI: 10.1590/s0074-02762002000200013
|View full text |Cite
|
Sign up to set email alerts
|

Descrição dos Ovos e dos Estádios Ninfais de Triatoma jurbergi Carcavallo, Galvão & Lent, 1998 Vistos Através de Microscopia Óptica e Eletrônica de Varredura (Hemiptera, Reduviidae)

Abstract: Description of Eggs and Nymphs of Triatoma jurbergi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
2
3
0
1
Order By: Relevance
“…Therefore, our results suggest that haplogroup 2 and haplogroup 3 at the physiological level are close haplogroups compared to haplogroup 1, and this is in agreement with results of genetic studies obtained with molecular markers (Bargues et al, 2008;Dorn et al, 2009;Monteiro et al, 2013;Gómez-Palacios et al, 2015). This suggests that at a sensory level these haplogroups can be considered a complex of species, as suggested by several authors, and supports the idea that in Mexico there are three haplogroups of the species T. dimidiata (Marcilla et al, 2001;Jurberg et al, 2005;Lehmann et al, 2005;Ibarra-Cerdeña et al, 2014;Galvão and Justi, 2015;May-Concha et al, 2015. Likewise, our results of antennal phenotype at sensory level and olfactory sensitivity analysis, separate the sexes from the three haplogroups.…”
supporting
confidence: 92%
“…Therefore, our results suggest that haplogroup 2 and haplogroup 3 at the physiological level are close haplogroups compared to haplogroup 1, and this is in agreement with results of genetic studies obtained with molecular markers (Bargues et al, 2008;Dorn et al, 2009;Monteiro et al, 2013;Gómez-Palacios et al, 2015). This suggests that at a sensory level these haplogroups can be considered a complex of species, as suggested by several authors, and supports the idea that in Mexico there are three haplogroups of the species T. dimidiata (Marcilla et al, 2001;Jurberg et al, 2005;Lehmann et al, 2005;Ibarra-Cerdeña et al, 2014;Galvão and Justi, 2015;May-Concha et al, 2015. Likewise, our results of antennal phenotype at sensory level and olfactory sensitivity analysis, separate the sexes from the three haplogroups.…”
supporting
confidence: 92%
“…The approximate average length of the T. guasayana eggs are like those described for Triatoma circummaculata (Stål, 1859) and Triatoma carcavalloi Jurberg, Rocha and Lent, 1998, species of the T. rubrovaria subcomplex [34,36]. It was also possible to show that the morphology of T. sordida sensu stircto eggs is similar to the morphology of T. matogrossensis Leite e Barbosa, 1953; T. vandae Carcavallo et al, 2002 and T. jurbergi Carcavallo, Galvão and Lent, 1998 [36][37][38]. Triatoma matogrossensis, T. vandae, and T. jurbergi were recently inserted together with the T. sordida subcomplex [7,8].…”
Section: Morphometry Of Eggssupporting
confidence: 56%
“…Morphometry showed a different range between the eggs of T. costalimai and T. jatai , with the former exhibiting the greatest length, but both were within the standard reported in a previous literature survey on some species of the genus Triatoma (Souza 2011). When length was compared to the morphometric data of other Triatoma species found in the Cerrado biome, we observed that the mean length of T. costalimai was closest to that of Triatoma guazu Lent and Wygodzinsky, 1979 ( X ̅ = 2.017 mm) (Silva et al 2000), Triatoma jurbergi Carcavallo, Galvão and Lent, 1998 ( X ̅ = 2.27 mm) (Jurberg et al 2002), Triatoma vandae Carcavallo, Jurberg, Rocha, Galvão, Noireau & Lent, 2002 ( X ̅ = 2.2 mm), and T. williami ( X ̅ = 2.1 mm) (Silva et al 2005), here as the mean length of T. jatai was closer to that of Triatoma baratai Carcavallo & Jurberg, 2000 ( X ̅ = 1.835 mm) (Rocha et al 2009) and Triatoma matogrossensis Leite and Barbosa, 1953 ( X ̅ = 1.64 mm) without the OP (Jurberg and Vogel 1994).…”
Section: Discussionmentioning
confidence: 87%